Making drug harms: Punishments for drugs offenders who pose risks to children. (November 2019) - Flacks, Simon
Images of children are routinely used in discourses on drugs, offering a compelling rationale for adopting particular policy positions or legislative reforms. However, the importance of childhood to the constitution of drug harms, and the punishment and subjectification of drug users and offenders, have rarely been the subject of enquiry, whether within drug and alcohol studies, criminology or legal studies. Scholarship on criminal sentencing in England and Wales is also relatively sparse, and has been dominated by analyses of the 'legal-rational' logic of particular provisions or reforms. This paper, which relies on the premise that drugs and their effects are constituted through discourse, and are thus contingent, variable and unstable, identifies the 'collateral realities' (Law, 2011) that are enacted during legislative and judicial attempts to stabilize the harms caused by drugs to children and communities.